Determinants of Dividend Policy in Compass 100 Index Companies - Yustika Dwi Novia; Marlina Marlina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The writing in this study is a quantitative study that has the aim of knowing what are the determinants of dividend policy on the Kompas 100 Index companies. Companies that are included in the Kompas 100 Index during the 2015-2019 period are the objects of this research. A total of 31 companies were used as research samples by using the purposive sampling technique method. The tool used to analyze the data in this research is Microsoft Excel 2010 and test hypotheses using panel data regression analysis with Eviews 12.0 program and a significance level of 5%. The results of the study based on partial sample testing indicate that liquidity and leverage have no effect on dividend policy, and profitability has a significant negative effect on the company's dividend policy.